Relevance of Neutrophil Neprilysin in Heart Failure - Suriya Prausmüller (MDPI AG, 2021)
Significant expression of neprilysin (NEP) is found on neutrophils, which present the transmembrane integer form of the enzyme. This study aimed to investigate the relationship of neutrophil transmembrane neprilysin (mNEP) with disease severity, adverse remodeling, and outcome in HFrEF. In total, 228 HFrEF, 30 HFpEF patients, and 43 controls were enrolled. Neutrophil mNEP was measured by flow-cytometry. NEP activity in plasma and blood cells was determined for a subset of HFrEF patients using mass-spectrometry. Heart failure (HF) was characterized by reduced neutrophil mNEP compared to controls (p < 0.01). NEP activity on peripheral blood cells was almost 4-fold higher compared to plasma NEP activity (p = 0.031) and correlated with neutrophil mNEP (p = 0.006). Lower neutrophil mNEP was associated with increasing disease severity and markers of adverse remodeling. Higher neutrophil mNEP was associated with reduced risk for mortality, total cardiovascular hospitalizations, and the composite endpoint of both (p < 0.01 for all). This is the first report describing a significant role of neutrophil mNEP in HFrEF. The biological relevance of neutrophil mNEP and exact effects of angiotensin-converting-enzyme inhibitors (ARNi) at the neutrophil site have to be determined. However, the results may suggest early initiation of ARNi already in less severe HF disease, where effects of NEP inhibition may be more pronounced.